Penerapan Pendekatan Discovery untuk Meningkatkan Aktivitas dan Hasil Belajar IPA Materi Organ Ekskresi pada Manusia dan Fungsinya di Kelas VIII-5 SMP Negeri 1 Bandar Lampung - Herwanto, Yuni (Lentera: Jurnal Ilmiah Kependidikan, 2022)
The purpose of this research is the discovery approach to improve student activity and learning outcomes in science learning on the material of excretory organs in humans and their functions for class VIII-5 students of SMP Negeri 1 Bandar Lampung. The method used in this research is Action Research which consists of 2 (two) cycles, and each cycle consists of: Planning, Implementation, Observation, and Reflection. Based on the results of action research that the application of the discovery approach to increase student activity and learning outcomes in science learning on the material of excretory organs in humans and their functions in class VIII-5 SMP Negeri 1 Bandar Lampung. Furthermore, the researcher recommends: (1) For teachers who have the same difficulty the discovery approach to increase student activity and learning outcomes in science learning on the material of excretory organs in humans and their functions; (2) In order to get maximum results, it is hoped that teachers will make PBP more interesting and varied.